Does the ECB rely on a Taylor rule? Comparing ex-post with real time data - Ansgar Belke; Jens Klose (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We assess the differences that emerge in Taylor rule estimations for the ECB when using ex-post data instead of real time forecasts and vice versa. We argue that previous comparative studies in this field mixed up two separate effects. First, the differences resulting from the use of ex-post and real time data per se and, second, the differences emerging from the use of non-modified real time data instead of realtime data based forecasted values and vice versa. Since both effects can influence the reaction to inflation and the output gap either way, we use a more clear-cut approach to disentangle the partial effects. Our estimation results indicate that using real time instead of ex post data leads to higher estimated inflation coefficients while the opposite is true for the output gap coefficients. If real time data forecasts for the current period are used (since actual data become available with a lag), this empirical pattern is even strengthened in the sense of even increasing the inflation response but lowering the reaction to the output gap while the reverse is true if true forecasts of real time data for several periods are employed.
Keywords: E43; E58; 330; European Central Bank; monetary policy; real time data; Taylor rule; Geldpolitik; Taylor-Regel; Schätzung; EU-Staaten